Measuring the effectiveness of contingency management intervention on patients’ treatment engagement and internal motivation: A randomized controlled trial - Ghani M.S.A.; Abdullah H.S.L.; Amat M.I. (Gyandhara International Academic Publications, 2024)
Indexed by SCOPUS